2014
DOI: 10.1007/s11205-014-0678-7
|View full text |Cite
|
Sign up to set email alerts
|

Are People Who Participate in Cultural Activities More Satisfied with Life?

Abstract: Abstract:The influence of various aspects of life on wellbeing has been extensively researched. However, despite little empirical evidence, participation in leisure activities has been assumed to increase subjective wellbeing. Leisure is important because it is more under personal control than other sources of life satisfaction. This study asked whether people who participate in cultural leisure activities have higher life satisfaction than people who do not, if different types of leisure have the same influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
3
29
0
5
Order By: Relevance
“…For example, spending on technology or indulgence was not associated with any dimension of well-being among the older adults. This supports Brown et al (2015), who found that only active, not passive, leisure activities were linked to better well-being. Elliot et al (2014) also reported that use of technology was not associated with well-being among older adults.…”
Section: Discussionsupporting
confidence: 83%
“…For example, spending on technology or indulgence was not associated with any dimension of well-being among the older adults. This supports Brown et al (2015), who found that only active, not passive, leisure activities were linked to better well-being. Elliot et al (2014) also reported that use of technology was not associated with well-being among older adults.…”
Section: Discussionsupporting
confidence: 83%
“…Leadbetter and O'Connor (2013) also found a significant association between strong life satisfaction and participation in social leisure activities, either because the physical activity linked to these events improves one's health or because social interactions derived from these activities improve one's life satisfaction. Brown et al (2015) contend that an increase in life satisfaction reflects the social interactions generally involved in these activities. In the negative affect component of SWB, the effect size was medium, and in positive affect large.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been related to life satisfaction and positive emotions among employees (Edmunds et al 2013), satisfaction with life among adolescents (Valois et al 2004), or personal well-being in cyclists (Lovretic et al 2013). Individuals who participate in sports also report higher life satisfaction compared to individuals who prefer sedentary leisure activities predictive (Brown et al 2015). Physical activity has also been related to positive affect (Mata et al 2012).…”
Section: Subjective Well-being and Physical Activitymentioning
confidence: 99%
“…In this study, we examined the focusing effects of physical activity ratings on subjective well-being assessments. Physical activity has often been presented as a precursor to a happy life (e.g., Brown et al 2015;Hogan et al 2015). Yet, little is known to what extent physically active people report higher well-being which might be biased by focusing effects.…”
Section: Introductionmentioning
confidence: 99%